Filling a Niche in "Ligand Space" with Bulky, Electron‐Poor Phosphorus(III) Alkoxides. Issue 9 (11th January 2019) - Hussein, Sharifa; Priester, Denis; Beet, Paul; Cottom, Jonathon; Hart, Sam J.; James, Tim; Thatcher, Robert J.; Whitwood, Adrian C.; Slattery, John M.
Abstract: The chemistry of phosphorus(III) ligands, which are of key importance in coordination chemistry, organometallic chemistry and catalysis, is dominated by relatively electron‐rich species. Many of the electron‐poor P III ligands that are readily available have relatively small steric profiles. As such, there is a significant gap in "ligand space" where more sterically bulky, electron‐poor P III ligands are needed. This contribution discusses the coordination chemistry, steric and electronic properties of P III ligands bearing highly fluorinated alkoxide groups of the general form PRn (OR F )3− n, where R=Ph, R F =C(H)(CF3 )2 and C(CF3 )3 ; n= 1–3. These ligands are simple to synthesize and a range of experimental and theoretical methods suggest that their steric and electronic properties can be "tuned" by modification of their substituents, making them excellent candidates for large, electron‐poor ligands. Abstract : Filling the gaps : A comprehensive overview of the synthesis, stereoelectronic properties and coordination chemistry of large, electron‐poor P III ligands bearing highly fluorinated alkoxides is described.